Intellectual capital and anticipated future sales in small and medium-sized biotechnology companies - Raine Hermans; Ilkka Kauranen (The Research Institute of the Finnish Economy (ETLA), 2003)
The objective of the study is to empirically verify impacts of intellectual capital to the anticipated future sales of small and medium-sized companies within biotechnology industry. Intellectual capital is divided into the following three categories: human, structural, and relational capital. Theoretically, a balanced interaction between the three categories implies value creation potential, and high anticipated sales of the company. In the empirical setting, survey data of small and medium-sized Finnish biotechnology companies is employed. The econometric procedure contains two stages. First, the interaction between three intellectual capital categories is estimated in factor analysis. Second, regression analysis is applied for explaining the anticipated future sales. The interactions within the three categories of intellectual capital explain two thirds of the variations in the anticipated future sales within 5 years. As a result, a well-balanced combination of human capital, structural capital, and relational capital seems to contribute to the highest anticipated sales levels. – – Tutkimuksen tarkoituksena on empiirisesti tuoda esille niitä vaikutuksia, joita osaamispääomalla on tulevaan ennakoituun liikevaihtoon pienissä ja keskisuurissa biotekniikan alan yrityksissä. Osaamispääoma jaetaan seuraaviin kolmeen osa-alueeseen: inhimillinen pääoma, rakenteellinen pääoma ja suhdepääoma. Teoreettisesti ajatellen näiden kolmen osa-alueen tasapainoinen vuorovaikutus mahdollistaa lisäarvon luomisen ja antaa yritykselle edellytyksiä saavuttaa korkea ennakoitu liikevaihto. Tutkimuksen empiirisessä osassa hyödynnetään suomalaisista pienistä ja keskisuurista biotekniikan alan yrityksistä kerättyä haastatteluaineistoa. Tutkimuksen ekonometrisessä tarkastelussa on kaksi vaihetta. Ensiksi, osaamispääoman eri osa-alueiden vuorovaikutusta pyritään arvioimaan faktorianalyysin avulla. Toiseksi regressioanalyysiä sovelletaan ennakoidun tulevan liikevaihdon selittämiseksi. Osaamispääoman kolmen osa-alueen vuorovaikutus selittää kaksi kolmannesta ennakoidun liikevaihdon vaihtelusta tulevien 5 vuoden aikana. Keskeisenä tuloksena on, että inhimillisen pääoman, rakenteellisen pääoman ja suhdepääoman tasapainoinen yhdistelmä näyttäisi mahdollistavan sen, että ennakoitu liikevaihto kasvaa kaikkien korkeimmaksi.
Keywords: 330; Biotechnische Industrie; Klein- und Mittelunternehmen; Humankapital; Finnland; Wissensmanagement